The Olmsted Parks of Louisville : A Botanical Field Guide - Haragan, Patricia Dalton, 1953- (Book collections on Project MUSE., 2014)
Frederick Law Olmsted, popularly known as the ""Father of American Landscape Architecture, "" is famous for designing New York City's Central Park, the U.S. Capitol grounds, and the campuses of institutions such as Stanford University and the University of Chicago. His celebrated projects in Boston, Buffalo, Detroit, Milwaukee, and other cities led to a commission from the city of Louisville, Kentucky, in 1891. There, he partnered with community leaders to design a network of scenic parks, tree-lined parkways, elegant neighborhoods, and beautifully landscaped estate gardens that thousands of.